DISCOURSE ANALYSIS OF THE REPRESENTATION OF DA'WAH VALUES IN THE INSTAGRAM CONTENT OF @hanan_attaki - Winda Kustiawan; Risky Azzahra; Muhammad Alfazar; Fauzi Iqbal (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
The development of digital technology has transformed the patterns of da'wah communication in the modern era, particularly through the use of social media as a medium for disseminating Islamic messages. This study aims to analyze the da'wah communication strategies employed by Ustaz Hanan Attaki through the Instagram platform. Using a qualitative approach and content analysis method, this research examines the form, style, and effectiveness of the da'wah messages conveyed through both visual and narrative content on the @hanan_attaki account. The findings reveal that Ustaz Hanan Attaki utilizes simple and relatable language, engaging visual elements, and contemporary themes that resonate with the lives of younger generations. His communication strategies include a personal approach, storytelling techniques, and the integration of religious symbols with modern lifestyle elements. These findings suggest that the integration of da'wah and digital media can enhance the reach and appeal of religious messages, particularly among millennial and Gen Z audiences. This research is expected to contribute to the development of Islamic preaching strategies that are relevant to the dynamics of new media.